1999
DOI: 10.1007/s004380050001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the ORF YBR264c in Saccharomyces cerevisiae, which encodes a new yeast Ypt that is degraded by a proteasome-dependent mechanism

Abstract: We identified the ORF YBR264c during the systematic sequencing of the Saccharomyces cerevisiae genome. It encodes a putative protein of 218 amino acids. We demonstrate here that the gene is indeed expressed and encodes a new Ypt in yeast. This protein specifically binds guanine nucleotides and interacts via its C-terminal end with the unique Rab GDP Dissociation Inhibitor (RabGDI). In accordance with a recent proposal, the gene is now designated YPT10. No mutant phenotype could be associated with inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The presence of a PEST sequence in a yeast small G protein has already been reported for the Ypt10 Rab protein. It has been shown that the Ypt10p PEST sequence played a role in protein stability, and that Ypt10p degradation is dependent on proteasome activity [32]. In a similar way, we suppose that the PEST sequence is implicated in vivo in regulating Rho5 protein abundance.…”
Section: Resultsmentioning
confidence: 55%
“…The presence of a PEST sequence in a yeast small G protein has already been reported for the Ypt10 Rab protein. It has been shown that the Ypt10p PEST sequence played a role in protein stability, and that Ypt10p degradation is dependent on proteasome activity [32]. In a similar way, we suppose that the PEST sequence is implicated in vivo in regulating Rho5 protein abundance.…”
Section: Resultsmentioning
confidence: 55%
“…These data suggest that the tagged Ypt7p can function equivalently to the untagged protein. No functions have been described for the Rab protein Ypt10p or Ypt11p, and mutants with deletions of the genes encoding either protein have no apparent phenotype; however, Ypt10p is known to be deleterious to cell growth when overexpressed (38). We asked whether the overexpression of GFP-YPT10 would result in similar growth inhibition.…”
Section: Resultsmentioning
confidence: 98%
“…Ypt10p is a Rab protein whose overexpression is growth inhibitory with possible defects in vesicular traffic (38) but otherwise mysterious; its localization has not been determined. Our bioinformatics analysis did not reveal Ypt10p to be a member of a large subclass of Rab proteins.…”
Section: Vol 26 2006 Evolutionary Conservation Of Rab Localization mentioning
confidence: 99%
See 1 more Smart Citation
“…A balanced ratio between the many actors in the secretory pathway (6) may therefore be critical for normal growth. In fact, toxic effects have been observed upon overexpression of YPT10 in S. cerevisiae, apparently due to alteration of structures in the Golgi apparatus (21). On the other hand, overproduction of wild-type Sec4p in C. albicans did not affect growth, while mutant forms behave as dominant-negative alleles (6,14,22).…”
Section: Discussionmentioning
confidence: 99%